Investigation of electrical conductivity of titanium dioxide nanofluids. (1st January 2011) - Sikdar, Sudipta; Basu, Somnath; Ganguly, Suvankar
Results from the experimental measurements of electrical conductivity of water based titanium dioxide nanofluid have been presented. Stable nanofluids of different concentrations, by mixing TiO 2 nanoparticles of different masses in water, have been prepared by ultrasonic vibration and magnetic stirring. Nanoparticle suspensions show monotonically increasing trend of electrical conductivity with the increase in temperature. However, the rate of increase of the electrical conductivity decreases with temperature at a particular concentration. A comparison of two parameter based correlation for the electrical conductivity has been developed to show the dual effect of temperature and concentration on electrical conductivity of titanium dioxide-water nanofluid.